The MUSE Ultra Deep Field (MUDF) – I. Discovery of a group of Lyα nebulae associated with a bright z ≈ 3.23 quasar pair. (7th March 2019) - Lusso, E; Fumagalli, M; Fossati, M; Mackenzie, R; Bielby, R M; Arrigoni Battaia, F; Cantalupo, S; Cooke, R; Cristiani, S; Dayal, P; D'Odorico, V; Haardt, F; et al.
ABSTRACT: We present first results from Multi Unit Spectroscopic Explorer (MUSE) observations at the Very Large Telescope in the MUSE Ultra Deep Field (MUDF), a ≈1.2 × 1.4 arcmin 2 region for which we are collecting ≈200 hours of integral field spectroscopy. The ≈40-h observation completed to date reveals the presence of a group of three Lyα nebulae associated with a bright quasar pair at z ≃ 3.23 with projected separation of ≈ 500 kpc . Two of the nebulae are physically associated with the quasars which are likely powering the Lyα emission, and extend for 100 kpc at a surface brightness level of ≈6 × 10 −19 erg s^-1 cm^-2 arcsec^-2 . A third smaller (≈35 kpc) nebula lies at a velocity offset of ≈1550 km s −1 . Despite their clustered nature, the two large nebulae have properties similar to those observed in isolated quasars and exhibit no sharp decline in flux at the current depth, suggesting an even more extended distribution of gas around the quasars. We interpret the shape and the alignment of the two brighter nebulae as suggestive of the presence of an extended structure connecting the two quasar host galaxies, as seen for massive galaxies forming within gas-rich filaments in cosmological simulations.